Design and development of a dexterous soft-robotics based assistive exoglove with kinematic modeling - Nawara Mahmood Broti; Shamim Ahmed Deowan; A.S.M. Shamsul Arefin (Intelligent Systems with Applications)
Necessity of a fully functional hand in our life is beyond description. Yet, a portion of the population is unable to move and control their hand due to paralysis. An assistive device can aid both daily activities and rehabilitation. This paper presents a dexterous soft robotics-based assistive glove with spatial kinematic model and control system. Unlike existing designs, our proposed five-fingered glove provides 20 degrees of freedom (DoFs), closely resembling a human hand. Each finger has 4 DoFs with controlled flexion, extension, abduction, and adduction motion ability. The tendon-driven mechanism simplifies design and control, while 3D-printed thermoplastic polyurethane (TPU) material ensures comfort, lightness, and an anthropomorphic appearance. The derived forward and inverse kinematics of each finger are capable of mapping joint angles to fingertip positions and orientations. To validate the kinematic model, virtual simulation was conducted to confirm its accuracy; while basic hand functionality experiments proved the gloves’ effectiveness. We expect this research to contribute to medical robotics, biomechanics, and assistive technology.